ENTREPRENEURIAL PERCEPTION AND MOTIVATION OF VOCATIONAL HIGH SCHOOL STUDENTS IN PURWOKERTO - Nabilla Khansa Naura; Nanang Martono; Elis Puspitasari (Universitas Padjadjaran, 2022)
This paper is the research result that aims to describe the entrepreneurial perception and motivation of vocational high school students in Purwokerto. The topic is mainly brought by the increasing unemployment rate in Indonesia and the rise of job competition after the ASEAN Economic Community. Consequently, the vocational education role could necessarily have prepared individuals to acquire the industry’s qualification. However, the system needs to be adequately improved to hone skills while making money. This research design is the quantitative method, using a survey to examine vocational high school students’ entrepreneurial perception and motivation at two state vocational high schools in Purwokerto. The author randomly took the twelfth grader as the sample. To analyze the data, the author used the descriptive method by using frequency distribution to display the frequency of various selection outcomes. The findings show that 77.8 percent of respondents possess a positive entrepreneurial perception. On the other side, 78.8 percent of respondents have high entrepreneurial motivation. Nonetheless, vocational students’ unreadiness still becomes the main roadblock, causing them to choose to look for a job over setting up a business. Strategic action is needed so that they would not only be confident but ready to create opportunities in the job field.